Legal Analysis of Exemption from Obstetrician's Duties from the Perspective of Fiqh Siyasah Qadhaiyyah (PTUN Study NO. 55/G/2023/MDN.) - Meuraxa, Yulia Inshiroh; Suparmin, Sudirman (IHSA Institute, 2025)
The presence of Dr. Erwynson in the RDP was the reason for the Dairi Regent to impose a disciplinary penalty in the form of a 12-month dismissal from office, on the basis of alleged violation of Article 4 letter C of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. Fiqh Siyasah Qadhaiyyah, which regulates the procedures for trial in Islamic law, emphasizes the principles of al-'adalah (justice) and al-maslahah (public interest). This study aims to analyze the Medan PTUN decision Number 55/G/2023/PTUN.MDN regarding the dismissal of Dr. Erwynson Saut Halomoan Simanjuntak by the Dairi Regent, with a normative legal approach through the Siyasah Qadhaiyyah perspective. This approach examines positive legal decisions and the principles of justice in Islam, especially regarding the authority of public officials to take administrative actions. The primary data used include PTUN decisions and relevant laws and regulations, while secondary data include legal literature and Fiqh Siyasah studies. The results of the study indicate that the dismissal of Dr. Erwynson is not in accordance with the principles of justice in both state administrative law and Islamic law. This study offers a critical view of the application of the principle of justice in administrative actions in Indonesia